The effect of resistance band training on the speed of athletes' sickle kicks - Karim, Ibnul; Wahyudi, Heri; Sulistyarto, Sony; Putera, Shidqi Hamdi Pratama (Sriwijaya Journal of Sport, 2026)
Research Problems: This study addresses the low speed of roundhouse kicks among Cham Petarung Sang Juara Pencak Silat athletes, a condition that can reduce attack effectiveness because slower kicks are more easily anticipated by opponents during competition. This issue is important to investigate, as kick speed is a crucial physical component that significantly influences athletic performance and competitive outcomes in pencak silat. Research Objectives: This study aimed to determine the effect of resistance band training on improving roundhouse kick speed in pencak silat athletes. Methods: A pre-experimental research design using a one-group pretest-posttest design was employed. The participants consisted of 10 pencak silat athletes selected through a total sampling technique. Resistance band training was used as the independent variable, while roundhouse kick speed served as the dependent variable and was measured using a 10-second kicking test. Data were analyzed using a paired t-test to examine differences in performance before and after the training intervention. Results: The results showed an increase in the mean kick speed score from 17.2 in the pretest to 21.5 in the posttest, with statistical analysis indicating a significant effect of resistance band training on kick speed improvement (p = 0.001; p < 0.05). Conclusion: This study concludes that resistance band training is effective in enhancing leg muscle strength and explosive power, which subsequently leads to increased roundhouse kick speed in pencak silat athletes. These findings contribute to the practical field of sports training by providing evidence-based support for coaches in developing more effective and varied training programs. Future research is recommended to include a control group and a larger sample size to strengthen causal conclusions and expand the generalizability of the findings.